Membangun Keterampilan Bertani Berlandaskan Alkitab - Yusak Agus Setiawan (LPPM - STT Kadesi Bogor, 2024)
This article explores the complex relationship between biblical concepts and agriculture, suggesting that agriculture is more than just a physical endeavour but rather a spiritual journey that reflects humanity's relationship with the Creator and creation. It starts with the fundamental duty to care for the planet and looks at the consequences of human wrongdoing on our ecological relationship. The article goes on to explain community-based methods that integrate biblical principles with agricultural knowledge. These methods include counselling, job training, and field assistance. It also clarifies how social pedagogy can be incorporated into agricultural frameworks to improve interpersonal skills and community understanding. By means of a discourse analysis and outcome analysis, it highlights the numerous benefits of integrating Biblical ethos with agricultural methods, particularly in terms of enhancing social welfare and strengthening religious beliefs. In conclusion, it claims that.